Efficacy and safety of DEB-TACE combined with transarterial TQB2450 infusion and oral Anlotinib as first-line treatment in advanced hepatocellular carcinoma: a single-arm phase II study - Yuan, Hang; Li, Yan; Zhao, Ke; Zhao, Ya-Nan; Yao, Quan-Jun; Geng, Xiang; Wang, Li-Feng; Song, Ho-Young; Hu, Hong-Tao (Frontiers in Immunology, 2025)
PurposeAdvanced hepatocellular carcinoma (HCC) remains difficult to treat due to high tumor burden and limited systemic options. This study evaluated the efficacy and safety of drug-eluting bead transarterial chemoembolization (DEB-TACE) combined with intra-arterial infusion of PD-L1 inhibitor TQB2450 and oral Anlotinib as first-line treatment in patients with advanced HCC.MethodsIn this prospective, single-arm phase 2 trial, 31 patients with BCLC stage C HCC received DEB-TACE, transarterial infusion of TQB2450 (1200 mg every 3 weeks), and oral Anlotinib (12 mg/day, 2 weeks on/1 week off). Tumor responses were assessed using mRECIST criteria. Primary endpoint was objective response rate (ORR); secondary endpoints included progression-free survival (PFS), overall survival (OS), and safety.ResultsThe ORR was 54.5%, with 3 patients (9.7%) achieving complete response. The median PFS and OS were 5.1 and 9.6 months, respectively. The most common grade ≥3 adverse events were thrombocytopenia (16.1%) and elevated bilirubin (12.9%). Most toxicities were manageable.ConclusionsThis triple-combination therapy demonstrated potentially beneficial antitumor activity and an acceptable safety profile in patients with advanced HCC. These findings support further investigation in randomized controlled trials.Clinical trial numberChinese Clinical Trials Database (ChiCTR2200056222).